How to handle oligometastatic disease in nonsmall cell lung cancer - Eichhorn, Florian; Winter, Hauke (European respiratory review, 2021)
Patients with nonsmall cell lung cancer and limited metastatic disease have been defined as oligometastatic if local ablative therapy of all lesions is amenable. Evidence from different clinical retrospective series suggests that this subgroup harbours better prognosis than other stage IV patients. However, most reports have included patients with inconsistent numbers of metastases in different locations treated by a variety of invasive and noninvasive therapies. As long as further results from randomised clinical trials are awaited, treatment decision follows an interdisciplinary debate in each individual case. Surgery and radiotherapy should capture a dominant role in the treatment course offering the option of a curative-intended local therapy in combination with a systemic therapy based on an interdisciplinary decision. This review summarises the current treatment standard in oligometastatic lung cancer with focus on an ablative therapy for both lung primary and distant metastases in prognostically favourable locations.